Addressing the human resources crisis: a case study of the Namibian health service - McCourt, Willy (BioMed Central, 2007)
BACKGROUND: This paper addresses an important practical challenge to staff management. In 2000 the United Nations committed themselves to the ambitious targets embodied in the Millennium Development Goals (MDGs). Only five years later, it was clear that poor countries were not on track to achieve them. It was also clear that achieving the three out of the eight MDGs that concern health would only be possible if the appropriate human resources (HR) were in place. METHODS: We use a case study based on semi-structured interview data to explore the steps that Namibia, a country facing severe health problems that include an alarmingly high AIDS infection rate, has taken to manage its health workers. RESULTS: In the fifteen years since independence, Namibia has patiently built up a relatively good strategic framework for health policy in the context of government policy as a whole, including strong training arrangements at every level of health staffing, and it has brought HIV/AIDS under the strategic umbrella through its National Strategic Plan for HIV/AIDS. Its major weakness is that it has not kept pace with the rise in HIV/AIDS and TB infection: the community counselling service, still at the pilot stage at the time of this study, was the only specific response. That has created a tension between building long-term capacity in a strategic context and responding to the short-term demands of the AIDS and TB crisis, which in turn affects the ability of HR to contribute to improving health outcomes. CONCLUSION: It is suggested that countries like Namibia need a new paradigm for staffing their health services. Building on the existing strategic framework, it should target the training of 'mid-level cadres'. Higher-level cadres should take on the role of supporting and monitoring the mid-level cadres. To do that, they will need management training and a performance management framework for staff support and monitoring.